Annotations on Complex Patterns - Bottoni, Paolo; Parisi Presicce, Francesco (Electronic Communications of the EASST, 2013)
Modelers of systems often want to isolate specific parts of a model to be treated as a whole, for example to protect them from accidental changes,to constrain them to specific policies, or to identify them as instances of a general pattern. In particular, we study here the case in which these parts are annotated with information from some external model. In a previous paper, we have discussed the use of annotations on individual model elements, represented as nodes in a graph; in this paper we model annotation processes involving also annotations themselves or whole configurations. To address the latter problem, we enrich the notion of graph by introducing a third sort of elements, called boxes, encompassing subgraphs, and associate them with annotations, too. We show how annotations on boxes support the modeling of complex policies,adapting the previous constructions for notation-aware rewriting to include boxes. The paper illustrates these concepts on the concrete modeling scenario of an organisation with security and temporal annotations.